Peran Perlindungan Hukum dalam Menjamin Keselamatan Saksi dan Korban Tindak Pidana Pembunuhan - Kurnia Ningsih; Muhammad Darwis; Moch Alfatah Alti Putra; Putri Ajeng Burhan; Murdiono Murdiono (Jurnal Litigasi Amsir, 2025)
This research aims to determine the legal protection arrangements for witnesses and victims in criminal acts of murder and to determine the forms of legal protection for witnesses and victims in criminal acts of murder. This research uses a normative legal research method with a statutory approach. The types and sources of legal materials used are primary legal materials and secondary legal materials. Data analysis will be reviewed and analyzed qualitatively. The legal protection arrangements for witnesses and victims in criminal acts of murder consist of; 1) Undang-Undang Nomor 13 Tahun 2006 tentang Perlindungan Saksi dan Korban; 2) Kitab Undang-Undang Hukum Pidana (KUHP); 3) Kitab Undang-Undang Hukum Acara Pidana; 4) Undang-Undang Nomor 31 Tahun 2014 tentang Perubahan atas Undang-Undang Nomor 13 Tahun 2006 tentang Perlindungan Saksi dan Korban. Forms of legal protection for witnesses and victims in criminal acts of murder are; determine criminal threats for perpetrators of criminal acts, by providing compensation and rehabilitation, physical and psychological protection from threats, harassment, terror and violence from any party, providing a sense of security under the provisions of article 5, medical assistance and psychosocial and psychological rehabilitation assistance, Compensation and restitution, Witness and Victim Protection Agency (LPSK) Peraturan Nomor 2 Tahun 2020 tentang Permohonan Perlindungan Saksi dan Korban Tindak Pidana that is, it is specified in Pasal 3.